DNA-Dependent Protein Kinase Mediates YB-1 (Y-Box Binding Protein)-Induced Double Strand Break Repair. Issue 2 (8th December 2022) - Nöthen, Till; Sarabi, Mohsen Abdi; Weinert, Sönke; Zuschratter, Werner; Morgenroth, Ronnie; Mertens, Peter R.; Braun-Dullaeus, Ruediger C.; Medunjanin, Senad
Abstract : Background: DNA-PK (DNA-dependent protein kinase) is a stress-activated serine/threonine kinase that plays a central role in vascular smooth muscle cell proliferation and vascular proliferative disease processes such as neointimal formation. In this study, we link the activation of DNA-PK to the function of the transcription factor YB-1 (Y-box binding protein). Methods: To identify YB-1 phosphorylation by DNA-PK, we generated different YB-1-expressing vectors. YB-1 nuclear translocation was investigated using immunoblotting and immunofluorescence staining. For YB-1 activity, luciferase assays were performed. Results: We show by mutational analysis and kinase assay that the transcriptional regulator YB-1 is a substrate of DNA-PK. Blockade of DNA-PK by specific inhibitors revealed its critical involvement in YB-1phosphorylation as demonstrated by inhibition of an overexpressed YB-1 reporter construct. Using DNA-PK-deficient cells, we demonstrate that the shuttling of YB-1 from the cytoplasm to the nucleus is dependent on DNA-PK and that the N-terminal domain of YB-1 is phosphorylated at threonine 89. Point mutation of YB-1 at this residue abrogated the translocation of YB-1 into the nucleus. The phosphorylation of YB-1 by DNA-PK increased cellular DNA repair after exposure to ionizing radiation. Atherosclerotic tissue specimens were analyzed by immunohistochemistry. The DNA-PK subunits and YB-1 phosphorylated at T89 were found colocalized suggesting their in vivo interaction. In mice, the local application of the specific DNA-PK inhibitor NU7026 via thermosensitive Pluronic F-127 gel around dilated arteries significantly reduced the phosphorylation of YB-1. Conclusions: DNA-PK directly phosphorylates YB-1 and, this way, modulates YB-1 function. This interaction could be demonstrated in vivo, and colocalization in human atherosclerotic plaques suggests clinical relevance of our finding. Phosphorylation of YB-1 by DNA-PK may represent a novel mechanism governing atherosclerotic plaque progression.